Avaliação do perfil oxidativo e da atividade de ectoenzimas em pacientes com neoplasia intra-epitelial cervical - Maldonado, Paula Acosta (2008)
Uterine cancers are considered to be one of the most important malignant diseases of the female genital tract, preceded only by breast cancer. The tumor cells may produce oxidative disturbances as well as damage to the antioxidant system. Cancer may also induce alterations in blood coagulation, ranging anywhere from slight platelet activation to thrombus formation, which impair the quality of life of these patients. This study aimed to evaluate the influence of uterine cervix cancer and its treatments, such as conization and radiotherapy (RTX), on the possible development of thrombogenic processes, on the oxidative profile and on coagulation disorders. Variations in the oxidative profile were analyzed through the determination of parameters such as TBARS and protein carbonyl content and antioxidant defenses were determined from the activity of catalase and reduced glutathione (GSH). Thromboembolic disorders were evaluated by the activity of enzymes such as NTPDase, E-NPP and 5 -nucleotidase, since all of these are present in the platelet membrane, as well as the activity of ADA which has an important role in the degradation of adenosine, which in turn is known for possessing tumor promoting functions. The evaluation of oxidative and antioxidant parameters revealed that TBARS levels, protein carbonyl, GSH and the activity of catalase were enhanced in the non treated group when compared to the other groups. The increased levels of oxidants may reflect their enhanced production by tumor cells, since it is known that antioxidant levels are enhanced at the beginning of the neoplasic transformation in an attempt to neutralize the enhanced free radical production. As for the enzymes involved in the thrombogenic process, the results revealed a significant inhibition of NTPDase in groups treated for a long time ago by CNZ or RTX, when compared to the more recently treated groups and the control. The reduced ATP hydrolysis could be acting to prevent ADP formation, since this nucleotide is the main agent that promotes platelet aggregation. The reduced AMP hydrolysis in all the treated groups, may be a result of the reduced production of adenosine due to the effectiveness of the treatments. In the conization and RTX treated groups, E-NPP activity, both in serum and platelets, was reduced when compared to the control and non treated groups, which could be a reflection of reduced nucleotide degradation, due to the absence of tumor cells and, in turn, lower production of adenosine, which is a tumor promoting agent and is also the substrate for ADA. The probable absence of tumor cells due to the effectiveness of the treatments and the reduced adenosine concentration may be responsible for the reduced ADA activity found in the same groups. The inhibition of enzymes such as E-NPP, 5 -nucleotidase and ADA in all the treated groups may suggest the role of these enzymes in sequentially controlling the concentrations of nucleotides in the extracellular environment. NTPDase appears to be more sensitive to changes caused by the passing of time after the end of the treatments. We may say that the surgery itself causes greater alterations in enzymes such as E-NPP, 5 -nucleotidase and ADA from platelets, because in the groups recently treated by CNZ these activities were enhanced as compared with the group recently treated by RTX, possibly as a result of platelet alteration, which would be responsible for the enzymatic alterations observed. NTPDase is more involved in the control of platelet aggregation and the enzymes 5`-nucleotidase, E-NPP and ADA are more involved in controlling adenosine concentrations.